Use of Tranexamic Acid (TXA) on reducing blood loss during scoliosis surgery in Chinese adolescents. Issue 1 (December 2015) - Ng, Bobby; Chau, WW; Hung, Alec; Hui, Anna; Lam, Tze; Cheng, Jack
Abstract Background Many reports had been received on the application of antifibrinolytic medications on spinal corrective surgery and the surgical outcome evaluations of its efficacy on reducing blood loss. This study aimed to assess the efficacy of tranexamic acid (TXA) in reducing operative blood loss during posterior spinal fusion for the treatment of severe adolescent idiopathic scoliosis (AIS). Methods A retrospective cohort study was carried out on 90 (TXA = 55, Control = 35) AIS girls undergoing posterior spinal surgery. Patients in TXA group used TXA as an antifibrinolytic agent to reduce blood loss, while control group did not. Blood loss, haemoglobin change and amount of blood transfused was estimated from intraoperative measurement by anaesthesiologists. Demographics were compared using Student'sT -test or Chi-square test where appropriate. Linear regression modelling was carried out between the use of TXA and total blood loss with controlling of confounding factors. Results Mean age and mean maximum major curve were 15.2 and 73°, and 15.3 and 63° in TXA and control groups respectively. TXA group showed significantly less intra-operative blood loss than the control group from intraoperative measurement (1.8 L vs. 3.9 L, p  < 0.01) and volume of cell saver blood transfused back to patients (0.6 L vs. 1.7 L, p  < 0.01). TXA group also showed significantly shorter total time taken for surgery (437 min vs. 502 min, p  < 0.01), and total blood loss per surgical segment level (0.1 L vs. 0.3 L, p  < 0.01). Regression models showed that the use of TXA decreased total blood loss by 794.3 ml after adjusting for maximum major curve, age, number of segments fused, bone graft, clotting capability, and infusion of coagulation factors. Conclusions Patients undergoing posterior spinal corrective surgery with the use of TXA showed much reduced total blood loss, reduced use of transfused blood, much less cell saver blood transfused back to the patient. The total blood loss was decreased by after using TXA after controlling for maximum major curve, age, surgical parameters, clotting capability, and infusion of coagulation factors.